Inhibition of Perforin-Mediated Neurotoxicity Attenuates Neurological Deficits After Ischemic Stroke - Pan, Yuhualei; Tian, Dan; Wang, Huan; Zhao, Yushang; Zhang, Chengjie; Wang, Song; Xie, Dan; Zhang, Dong; Zhu, Yanbing; Zhang, Yongbo (Frontiers in Cellular Neuroscience, 2021)
Perforin-mediated cytotoxicity plays a crucial role in microbial defense, tumor surveillance, and primary autoimmune disorders. However, the contribution of the cytolytic protein perforin to ischemia-induced secondary tissue damage in the brain has not been fully investigated. Here, we examined the kinetics and subpopulations of perforin-positive cells and then evaluated the direct effects of perforin-mediated cytotoxicity on outcomes after ischemic stroke. Using flow cytometry, we showed that perforin+CD45+ immune cells could be detected at 12 hours and that the percentage of these cells increased largely until on day 3 and then significantly declined on day 7. Surprisingly, the percentage of Perforin+CD45+ cells also unexpectedly increased from day 7 to day 14 after ischemic stroke in Perforin1-EGFP transgenic mice. Our results suggested that Perforin+CD45+ cells play vital roles in the ischemic brain at early and late stages and further suggested that Perforin+CD45+ cells are a heterogeneous population. Surprisingly, in addition to CD8+ T cells, NK cells, and NKT cells, central nervous system (CNS)-resident immune microglia, which are first triggered and activated within minutes after ischemic stroke in mice, also secreted perforin during ischemic brain injury. In our study, the percentage of perforin+ microglia increased from 12 hours after ischemic stroke, increased largely until on day 3 after ischemic stroke, and then moderately declined from day 3 to day 7. Intriguingly, the percentage of perforin+ microglia also dramatically increased from day 7 to day 14 after ischemic stroke. Furthermore, compared with wild-type littermates, Perforin 1-/- mice exhibited significant increases in the cerebral infarct volume, neurological deficits, and neurogenesis and inhibition of neurotoxic astrogliosis. Interestingly, the number of CD45+CD3+ T cells was significantly decreased in Perforin 1-/- mice compared with their wild-type littermates, especially the number of γδ T cells. In addition, Perforin 1-/- mice had lower levels of IL-17 than their wild-type littermates. Our results identified a critical function of perforin-mediated neurotoxicity in the ischemic brain, suggesting that targeting perforin-mediated neurotoxicity in brain-resident microglia and invading perforin+CD45+ immune cells may be a potential strategy for the treatment of ischemic stroke.